Does moving home affect residential heating decisions? Exploring heating fuel switching in Ireland - John A. Curtis; Gianluca Grilli (The Economic and Social Research Institute (ESRI), 2020)
Previous research finds that moving home can serve as a starting point for more sustainable living practices, specifically lower energy consumption. This research examines whether changes in occupancy or tenure at residential properties is also associated with decisions on overhauling a property's heating system. Properties are almost twice as likely to switch to gas as the primary heating fuel when occupancy changes. The likelihood almost quadruples when there is also a change in tenure. Beyond occupancy and tenure, family size is the most notable occupant characteristic associated with a higher likelihood of switching to gas. In properties with six or more family members, and where occupancy changes, the likelihood of switching to gas is 7 percentage points higher than properties with 1-2 family members. The research extends the understanding of energy-related decisions associated with moving home and that property owners are more likely to invest in energy retrofits during this transitional period. This creates the opportunity for certain policy supports to be designed.
Keywords: 330; Energiekonsum; Heizungsanlage; Wohnungswechsel; Irland